Experimental study of the interference in air curtains due to the parallel transfer in front of refrigerated display cases - Nascimento, Samuel Mariano do (2014)
Refrigerated display cases used to expose perishable food for sale in convenience stores and supermarkets are subject to human interference. Clients and repositories transit in front of display cases and frequently remove or place food products on the shelves depending on sales volume. This movement is part of the trade, although it has consequences on the display case performance. Each interference drags or breaks the air curtain resulting in the modification of air flow and promoting the ambient air thermal entrainment that consequently change the equipment's working conditions and increase 2% to 5% its energy consumption. This experimental study quantifies the air temperature increase and the energy consumption increase when there is an interference drag due to people inside the store passing parallel to the frontal opening of the display case. The tests were performed using a robotic mannequin that systematically transfers around the display case (5 minutes lap during 24 hours) and parallel to the frontal opening of the refrigerated display case with a translation velocity of 0.6 m/s. The results show that the products temperature increases 16% and the energy consumption increases 4.6% due to the air movement generated by the robotic mannequin transfer. These results are part of a more complex evaluation of the air curtain interference by humans to be used in the development of new products on an industrial scale.